Adverse Drug Reactions After Administration of Emodepside/Praziquantel (Profender®) in an MDR1-Mutant Australian Shepherd Dog: Case Report - Gaens, Daniela; Leithäuser, Carola; Hamann, Melanie; Geyer, Joachim (Frontiers in Veterinary Science, 2019)
A three-year-old male Australian Shepherd was presented with signs of neurological toxicity following the administration of Profender® at the recommended dosage. Unfortunately, the owner had received the product from a veterinarian without any further instructions on fasting as recommended by the manufacturer, so the dog was fed prior to Profender® administration. Neurological toxicity included generalized tremor, agitation and panting, and required hospitalization of the dog. All neurological signs resolved after symptomatic treatment within 24 hours and the dog was discharged without the need for further medication. MDR1 genotyping revealed a homozygous mutation of the MDR1 gene, which is normally important to prevent brain penetration of emodepside by an efflux-based transport mechanism at the blood brain barrier. This case indicates that Profender® can lead to serious, but transient neurological toxicity in dogs with homozygous MDR1 mutation even at therapeutic dosage, in particular when fasting recommendations are disregarded. Therefore, the case report highlights both the importance of MDR1 genotyping in predisposed dog breeds as well as strict compliance with fasting recommendations around the time of Profender® administration.